Masa Disintegrasi Pendidikan Islam (Masa Dinasti Fatimiyah): Sejarah Singkat Dinasti Fatimiyah, Pendidikan Islam Pada Dinasti Fatimiyah, Faktor Kemunduran Dinasti Fatimiyah - Nurul Azizatul Isnaini (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2023)
History records various conditions of the journey of the greatness of Islamic teachings to this day. The progress of various kinds of science and technology where at that time the Islamic world was used as a mecca for many people in terms of the development of education. The development of education explicitly recorded by history started from Islamic education during the time of Rasulullah SAW, then continued during the reign of his companions (Khulafaurasyidin), continued to the Umayyah, Abbasiyah dynasties until it arrived at the discussion of this journal, namely the Fatimiyah dynasty. In understanding the history of Islamic education during the Fatimiyah dynasty, it is necessary to have studies from various sources of knowledge, for this reason, researchers here use a type of literature study research, where the object of this research is the field of "History of Islamic Education", especially in the field of "The Period of Disintegration of Islamic Education". The Fatimiyah Dynasty", and this research model uses descriptive analysis research, in which the data approach comes from several accredited journals, books, and is obtained via the internet, then analyzed personally. The discussion also includes a brief history of the Fatimiyah dynasty, an overview of education in the Fatimiyah dynasty, and the decline of the Fatimiyah dynasty.